Prevalence and risk factors of hyperuricaemia in non-obese Chinese: a single-centre cross-sectional study - Chengfu Xu; Jinghua Wang; Xinyu Wang; Yishu Chen; Shenghui Chen; Haoliang Zhai (BMJ Open)
Objectives Hyperuricaemia is closely related to metabolic diseases and is receiving increasing attention from all over the world. This study aimed to investigate the prevalence and factors associated with hyperuricaemia in non-obese Chinese population.Design Retrospective cross-sectional study.Setting A large general hospital that can provide health check-ups in Hangzhou, China.Participants A total of 5731 apparently healthy Chinese adults (2349 men and 3382 women) who took their health check-ups during the year of 2019. Exclusion criteria: (1) those with body mass index ≥24 kg/m2; (2) those with incomplete anthropometric and biochemical data; (3) those with a history of malignancy and (4) those under urate-lowering treatment.Primary and secondary outcome measures The prevalence and factors associated with hyperuricaemia in non-obese Chinese adults.Results Of the 5731 non-obese subjects enrolled, 538 (9.4%) were identified as having hyperuricaemia, specifically 16.3% in men and 4.6% in women. The prevalence of hyperuricaemia markedly increased in women aged above 50 years. The prevalence of hyperuricaemia was significantly higher in metabolically unhealthy participants with normal weight than in metabolically healthy participants with normal weight. Participants with hyperuricaemia showed a higher prevalence of metabolic syndrome and fatty liver disease than participants with normouraemia. Age, waist circumference, estimated glomerular filtration rate, blood urea nitrogen, excessive drinking and fatty liver were associated with hyperuricaemia in both genders.Conclusion The prevalence of hyperuricaemia was 9.4% in non-obese Chinese adults. Non-obese participants with hyperuricaemia also showed multiple metabolic disorders. We suggest that clinicians pay attention to serum uric acid level in non-obese patients.